Design, data analysis and measurement uncertainty evaluation of an eddy-current sensor array for in-process metrology of carbon fiber reinforced plastics. Issue 1 (2019) - Haefner, Benjamin; Berger, Dietrich
Abstract: Composite lightweight components of carbon fiber reinforced plastics (CFRP) provide great potential for the automotive industry. Yet, due to their complexity, there is a high amount of quality defects in their production processes. Thus, this article deals with an approach for in-process metrology of CFRP components by means of an eddy-current sensor array. First, the development of the sensor design and its in-process integration is introduced. Second, a method for the quantitative evaluation of the measurement data as well as the measurement uncertainty is elaborated. Finally, a machine learning approach for the classification of crucial defects is shown.